Kisah Tanah Jawa: Jagad Lelembut Sebuah Novel Penguat Akidah dan Akhlak: An Amplifier Akidah and Akhlak Novel Kisah Tanah Jawa: Jagad Lelembut - Ferdian Achsani (Balai Bahasa Provinsi Papua, 2020)
The Kisah Tanah Jawa Jagad Lelembut is one of the novels which included an astral figures in the Javanese. This book described various invisible or astral creature figures. Based on these figures stories, this novel can be used to strengthen aqeedah and morals for the reader. This study aims to describe the aqeedah and morals values in the Kisah Tanah Jawa: Jagad Lelelmbut novel. This descriptive qualitative research uses reading, note taking and documentation techniques in the data collection process. The results showed that this novel can be used as a strengthened aqeedah to increase the faith in God or Allah and have faith in qada and qadar. In the good character aspect, this novel teaches the reader to always do good things such as giving alms, praying before going to sleep and being polite and maintaining cleanliness. This novel also teaches the reader to avoid despicable acts such as murder and adultery, as a despicable act.